2006
DOI: 10.1152/physiolgenomics.00224.2005
|View full text |Cite
|
Sign up to set email alerts
|

Distinct gene expression profiles in adult mouse heart following targeted MAP kinase activation

Abstract: Three major MAP kinase signaling cascades, ERK, p38, and JNK, play significant roles in the development of cardiac hypertrophy and heart failure in response to external stress and neural/hormonal stimuli. To study the specific function of each MAP kinase branch in adult heart, we have generated three transgenic mouse models with cardiac-specific and temporally regulated expression of activated mutants of Ras, MAP kinase kinase (MKK)3, and MKK7, which are selective upstream activators for ERK, p38, and JNK, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 41 publications
(57 reference statements)
2
33
0
1
Order By: Relevance
“…HRas G12V display HCM associated with interstitial fibrosis and sudden death (20)(21)(22). Cardiac-specific Nf1-deleted mice develop marked cardiac hypertrophy, progressive cardiomyopathy, and fibrosis as adults (71).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…HRas G12V display HCM associated with interstitial fibrosis and sudden death (20)(21)(22). Cardiac-specific Nf1-deleted mice develop marked cardiac hypertrophy, progressive cardiomyopathy, and fibrosis as adults (71).…”
Section: Figurementioning
confidence: 99%
“…Some data argue that excessive activity of this pathway causes HCM, whereas other evidence suggests involvement in physiological, but not pathological, hypertrophy (18,19). Transgenic mice with cardiac-specific expression of oncogenic HRas (G12V) display significant cardiac hypertrophy, decreased contractility, diastolic dysfunction associated with interstitial fibrosis, induction of cardiac fetal genes, and sudden death (20)(21)(22), all of which are consistent with HCM. In cultured cardiomyocytes, depletion of Erk1/2 with antisense oligonucleotides or pharmacological inhibition of Mek1/2 attenuates the hypertrophic response to agonist stimulation (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression profiling from temporally regulated V12H RAS transgenic hearts has suggested that induction of early response genes, loss of mitochondrial function and altered ionic channel proteins are the likely culprits of the pathological changes in extracellular matrix remodeling, cardiac output and electrophysiological parameters (96). Recent work has suggested that the selective induction of Gαi in the RAS transgenic heart contributes to impaired sarcoplasmic reticulum calcium cycling (97), and a number of other studies have led to descriptions of RAS-induced alterations in calcium transients (98)(99)(100).…”
Section: Cooperative Effects On the Ras Pathway: Cross-links In Hypermentioning
confidence: 99%
“…Beside that, in mouse heart Panx1 expression significantly increases as result of the selective ERK, p38 and JNK activations [116]. These findings were obtained in the high-throughput study of adult mice expressing activated mutants of Ras, MKK3 and MKK7 in the cardiac specific and temporally regulated fashion.…”
mentioning
confidence: 70%